Effect of actinomycete extract on experimental model of acute systemic bacteraemia of vancomycin resistant enterococcus in swiss albino rats - M.KALPANA DEVI,; R.USHA, (International Journal of Pharma and Bio Sciences, 2017)
Actinomycetes provide important bioactive compounds of high commercial value and continue to be routinely screened for new bioactive substances. The best actinomycetes isolate named as ACT 24 extract have antibacterial effect on the Staphylococcus aureus and E.coli with varying degrees in the range of 14-36mm. The isolate also shows good activity against tested organism Vancomycin Resistant Enterococcus (VRE) in the range of 26mm. This study is about the effect of ACT 24 against problematic organisms into the blood stream in Swiss albino rats. The present study was carried out in adult healthy Swiss albino rats. The control group shows no growth on enterococcal agar. In VRE induced group, the blood samples show more number of colonies on Enterococcal agar VRE were detected in almost all the organs of rat. ACT 24 treated rat organs were homogenised and plated on enterococcal agar, one or two colonies were observed and absence of apparent pathological changes. This study concludes with that ACT 24 extracts show good activity against VRE in rat model.